Ethnomedicinal plants used for the treatment of neurodegenerative diseases in Himachal Pradesh, India in Western Himalaya - Sharma, Kiran; Verma, Rachna; Kumar, Dinesh; Nepovimova, Eugenie; Kuča, Kamil; Kumar, Ashwani; Raghuvanshi, Disha; Dhalaria, Rajni; Puri, Sunil (Journal of ethnopharmacology, 2022)
ETHNOPHARMACOLOGICAL RELEVANCE: Medicinal plants are considered as a healthcare resource and widely used by rural people in their traditional medicine system for curing neurodegenerative diseases. Neurodegenerative diseases refer to incurable and debilitating conditions that result in progressive degeneration/death of nerve cells or neurons in the human brain. This review is mainly focused on the usage of different ethnomedicinal plants in the treatment of different neurodegenerative diseases in Himachal Pradesh. Study reveals total of 73 ethnomedicinal plants, which are used for treating different neurological disorders in different areas of Himachal Pradesh. The data is compiled from the different sources that described the detailed information of plants in tabular form and highlights the significance of different phytochemicals on neuroprotective function. The present study also provides the scientific data and clinical (in-vivo and in-vitro) studies in support of ethnomedicinal use. AIM OF THE STUDY: This review aims to provide information of ethnomedicinal plants which are used for the treatment of neurodegenerative diseases in Himachal Pradesh. MATERIALS AND METHODS: Information on the use of ethnomedicinal plants to treat various neurological disorders has been gathered from a variety of sources, including various types of literature, books, and relevant publications in Google Scholar, Research Gate, Science Direct, Scopus, and Pub Med, among others. The collected data is tabulated, including the botanical names of plants, mode of use and the disease for which it is used for curing, etc. RESULTS: There are 73 ethnomedicinal plants that are used to cure various neurological disorders, with the most plants being used to treat epilepsy problem in Himachal Pradesh. CONCLUSION: Numerous phytochemicals and extracts from diverse plants were found to have a protective effect against neurodegenerative diseases. Antioxidant activity is known to exist in a variety of herbal plants. The most common bioactive antioxidant chemicals having their significant impacts include flavonoids, flavones, coumarins, lignans, isoflavones, catechins, anthocyanins, and isocatechins.
Keywords: Neurodegenerative Diseases; fytonutrienty; Epilepsy; Antioxidants; Antioxidant; India; lidé; anthokyaniny; neurodegenerativní nemoci; Anthocyanins; tradiční lékařství; Ethnopharmacology; Humans; fytoterapie; Ethnomedicine; antioxidancia; Neuroprotection; etnofarmakologie; Phytochemicals; Medicine, Traditional; Indie; Cardiovascular diseases; Phytotherapy